"Good" things take time: a living story of research as "life". Issue 1 (27th November 2018) - Hurd, Fiona; Dyer, Suzette; Fitzpatrick, Mary
Abstract : Purpose: Although the process of fieldwork is often characterised by disorder, the requirement to adhere to a tightly defined methodology and produce timely research outputs often leads the authors to present the findings as though the research has been the product of a linear process. The purpose of this paper is to unmask this paradox, by documenting the disorder and development of a research project 15 years (so far) in duration. Design/methodology/approach: The approach used in this paper is one of auto-ethnographic reflection, drawing on aspects of Boje's living story approach, incorporating not only the "linear" narrative of the research process, but also fragments of ante-narrative, themes running above and below the dominant. Within the study, the authors are reflecting on, a range of qualitative methods, including interview, focus groups, memory-work, and living story (ante-narrative) methods, which are employed within a critical management research methodology. Findings: The authors' experiences show that although "messiness" may be an inherent part of qualitative research, it is this very disorder, and the consequent opportunities for time and space, that allows the research, and the researcher, "time to breathe". This reflexivity allows for methodological development and refinement, and ultimately rigorous and participative research, which also honours the participants. The authors argue that although this approach may not align with the current need for prolific (and rapid) publication, in allowing the disorder to "be" in the research, and allowing the time to reassess theoretical and methodological lenses, the resultant stories may be more authentic – both the stories gathered from participants and the stories of research. Originality/value: The paper highlights the intertwining of stories of participants and stories from research, which is a significant addition to understandings of the "messiness" of qualitative research. This paper adds to the growing call for the inclusion of "chaos" and authenticity in qualitative research, acknowledging and valuing the humanity of the researcher, and giving voice to the paradox between the time to methodologically develop, and the requirement for timely research.